Photodynamic therapy for skin rejuvenation: review and summary of the literature – results of a consensus conference of an expert group for aesthetic photodynamic therapy. (29th November 2012) - Karrer, Sigrid; Kohl, Elisabeth; Feise, Konstantin; Hiepe‐Wegener, Dagmar; Lischner, Stephan; Philipp‐Dormston, Wolfgang; Podda, Maurizio; Prager, Welf; Walker, Torsten; Szeimies, Rolf‐Markus
Summary Skin rejuvenating effects of photodynamic therapy (PDT) for photoaged skin has been well‐documented in several clinical trials. Different photosensitizers (5‐aminolevulinic acid, methyl aminolevulinate) and diverse light sources (light‐emitting diodes, lasers, intense pulsed light) have been used with promising results. An improvement of lentigines, skin roughness, fine lines and sallow complexion has been achieved with PDT. These clinically evident effects are at least in part due to histologically proven increase of collagen and decrease of elastotic material in the dermis. Effective improvement of photoaged skin, simultaneous treatment and possibly also prevention of actinic keratoses, the possibility of repeated treatments and, in contrast to other procedures, limited and calculable side effects make PDT a promising procedure for skin rejuvenation.